Correlation Between Nurses Workload and Work Stress in the Emergency Department - Hidayat, Taopik; Abdillah, Hadi; Hamidah, Ernawati; Hadiyanto, Hendri (Universitas Prima Indonesia, 2025)
Workload and work stress among nurses, especially in the Emergency Room (ER), are crucial issues that affect the quality of health services. This study aims to determine the relationship between nurses’ workload and work stress in the ER of Jampang Kulon Regional General Hospital. A quantitative correlational research design was used with a cross-sectional approach. The population consisted of 29 ER nurses, selected through total sampling. Data were collected using the NASA-TLX (Task Load Index) questionnaire to measure workload and a work stress questionnaire developed based on the HSE (Health and Safety Executive) standards. The results showed that 62.1% of nurses experienced a high workload, while 58.6% experienced moderate work stress. The Spearman rank test indicated a significant positive correlation between workload and work stress (p = 0.001; r = 0.642), meaning that an increase in workload is associated with an increase in work stress. This finding highlights the importance of workload management to reduce stress levels among nurses. Improving work scheduling, increasing staffing ratios, and providing regular stress management programs are recommended to enhance the nurses' well-being and service performance. In conclusion, there is a significant relationship between workload and work stress among nurses in the ER of Jampang Kulon Hospital.